Progress in research on the effects of environmental factors on natural forest regeneration - Liu, Jiabo (Frontiers in Forests and Global Change, 2025)
Forests cover approximately 31% of the Earth’s land area. They serve as critical habitats for the majority of terrestrial organisms. Natural regeneration is the main method for renewing forests. This process not only drives forest development but also plays a crucial role in maintaining ecosystem productivity, stabilizing community structure and conserving biodiversity. Current studies indicate that the natural forest regeneration process is influenced by a multitude of environmental factors, including light availability, water resources, wind patterns, soil properties, geography features and groundcover. Light strongly influences processes such as photosynthetic efficiency, biomass allocation and photoinhibition in tree growth. Temperature plays an important role in forest regeneration by influencing seed germination, seedling development, and nutrient cycling in the soil. Water availability regulates the competition between trees and other vegetation. Wind plays a key role in seed dispersal, and with the recovery process following wind disturbances potentially extending for 30–50 years. Soil composition, both physical and chemical, as well as biological factors such as microorganisms, directly determine the trajectory and efficiency of forest ecosystem recovery. Geo-environmental factors such as altitude and topography further shape regeneration by modifying climatic conditions and hydrothermal conditions. In addition, the groundcover layer can promote seed germination while also posing challenges to regeneration through resource competition or by promoting the spread of pathogens and pests. Despite significant advances, several gaps remain in the research: (1) Research on the effects of wind speed on trees’ physiological properties, such as growth and root stability, is limited; (2) Most existing studies primarily focus on seed-based regeneration, with relatively little attention given to coppicing regeneration; (3) There is a scarcity predictive ecological models for coping with future climate change. Addressing these gaps requires more comprehensive studies on the impact of wind factors on the physiological and ecological characteristics of seedlings and young trees to break through the bottleneck associated with natural regeneration. Furthermore, in-depth studies are needed on emergent plants resilience and their adaptability under varying light, soil and climate conditions. A systematic comparison of coppicing regeneration with seed-dependent regeneration is suggested to understand the advantages and challenges associated with different regeneration methods.